UPAYA PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF MODEL MAKE A MATCH - Faizah Basyir; Yulia Fatmianeri; Mardiati Mardiati (Math Educa Journal, 2022)
This study aims to determine the increasing in Mathematics learning activities using the Make a Match Model in class IX3 MTsN 2 Pasaman year  2018/2019. This research was conducted in class IX3 MTsN 2 Pasaman with 38 students. This research is a classroom action research with four stages, namely: planning, action, observation, and reflection. The learning model is the Make a Match Model. The results of this study are the increasing in student learning activities. In the first cycle, the average student learning activity was 69.79%. While in the second cycle, the average student activity became 86.45%. Student learning activities increased by 14.66%. With student learning activities caused student learning outcomes to increase. In the first cycle, the average class value was 67.9 with 16 students who completed the study out of 38 people. While in the second cycle, the average grade value increased to 76.3%. The percentage of student learning completeness in cycles I and II increased by 31.91%, from 16 people who completed cycle I to 29 people who completed cycle II. Based on the description above, the Make a Match Model can improve the learning activities of class IX.3 MTsN 2 Pasaman students in the Mathematics subject of Quadratic Equations. The increasing of student learning activities makes student learning outcomes also increasing.